(untitled) (The Review of Diabetic Studies, 2025)
Background: Oral diseases, primarily dental caries and periodontal disease, represent a massive global health burden, affecting approximately 3.5 billion people and accounting for significant economic expenditures, estimated at over US380 billion annually. In the prevailing healthcare model, oral health is frequently isolated from general medical practice, creating a "dental-medical divide." This separation disproportionately affects vulnerable populations—including children, pregnant women, the elderly, and individuals with chronic metabolic conditions—who face systemic barriers to accessing traditional dental care (Intervention 2). As a result, the standard of care often fails to capture early disease or manage the oral-systemic interface effectively. Integrating preventive oral healthcare into family medicine and general practice (Intervention 1) has been proposed as a transformative strategy to leverage the broad reach of primary care for early risk assessment, screening, and intervention. Objective: The primary aim of this systematic review is to systematically compare the effectiveness of integrated oral healthcare models delivered by non-dental primary care providers (Intervention 1) versus standard referral-based care or ad-hoc advice (Intervention 2) on key patient outcomes (caries increments, periodontal status, glycemic control, quality of life) and system efficiency (cost-effectiveness, referral adherence) for populations accessing primary care. Methods: A comprehensive systematic review was conducted adhering to PRISMA 2020 guidelines. Electronic databases (MEDLINE, Embase, Cochrane Library, CINAHL, and Scopus) were searched for randomized controlled trials (RCTs), cohort studies, and economic evaluations published through 2023. The PICO framework defined the Population as primary care patients; Intervention as oral health services (screening, fluoride varnish, education) provided by physicians, nurses, or midwives; Comparison as standard care; and Outcomes as clinical indicators (e.g., dmft/DMFT, HbA1c) and system metrics. Risk of bias was assessed using the Cochrane RoB 2.0 tool and the Newcastle-Ottawa Scale. Results: Forty-nine studies met the inclusion criteria, encompassing over 500,000 participants across pediatric, adult, and geriatric cohorts. In pediatric populations, integrated care models such as the "Into the Mouths of Babes" (IMB) program demonstrated a 17% reduction in caries-related treatments for children receiving ≥4 preventive visits by physicians, with significant cost-effectiveness. For adults with type 2 diabetes, bidirectional screening in primary care and dental settings effectively identified undiagnosed periodontitis and pre-diabetes, with periodontal therapy yielding a mean HbA1c reduction of 0.40%. However, referral adherence from medical to dental providers remained a critical bottleneck, often below 50% without structured navigation. Nurse-led interventions in nursing homes showed modest improvements in denture hygiene but struggled to sustain reductions in dental plaque due to institutional barriers. Conclusion: The integration of family medicine into preventive oral healthcare demonstrates clear superiority over standard care for specific high-risk populations, particularly in reducing early childhood caries and improving diagnostic rates for oral-systemic comorbidities. However, system efficiency is frequently compromised by lack of reimbursement parity, interoperability challenges, and workforce training gaps. The evidence supports a policy shift toward interprofessional "dental homes" within primary care, necessitating structural reforms to sustain these clinical gains.